The role of high-performance microwave absorbing materials in electromagnetic interference shielding: a review of the advanced internal design of polymer-based nano-composites - Elagib, Tienah H. H.; Kabbashi, Nassereldeen Ahmed; Mirghani, Mohamed Elwathig Saeed; Alam, Md. Zahangir; Al-Khatib, Ma'an Fahmi Rashid (University POLITEHNICA Timisoara, 2022)
Electromagnetic interference (EMI) shielding refers to the ability of a material to block the EM waves generated by electronic systems. In the past few decades, there has been sustained research in the use of conductive metal and conductive polymer-based shielding approaches, but these have shown difficulties with high density and processability. In recent years, other strategies have been developed to obtain more practical shielding materials. A summary of lightweight polymer-based nanocomposites with EM absorption characteristics for EMI shielding is provided. The advantages, disadvantages, and EMI shielding mechanisms of various types of nanocomposites are discussed. This article focused on understanding the approaches related to different types of fillers, which include carbon materials as well as metal particles and microwires which are used separately and in the form of hybrids designed to achieve highly effective shielding capabilities. This review focuses on structure configurations such as multilayer structures, coating, and advanced three-dimensional (3D) structures, which may be used to encourage the development of more environmentally responsible EMI shielding materials. In summary, it can be said that the thickness, dielectric, magnetic characteristics, and filler concentration, can be adjusted to obtain the desired combination of higher shielding performance and EM absorption properties.